Fenofibrate promotes PPARα-targeted recovery of the intestinal epithelial barrier at the host-microbe interface in dogs with diabetes mellitus - Katti R. Crakes (Nature Portfolio, 2021)
Abstract Diabetes mellitus (DM) is associated with a dysfunctional intestinal barrier and an increased risk for systemic infection and inflammation in people, though the pathogenic mechanisms leading to this are poorly understood. Using a canine model of DM, we showed that the peroxisomal proliferator-activated receptor-α agonist fenofibrate modulates plasma lipid profiles and markers of intestinal barrier function. A 3-week course of fenofibrate reduced fasting interstitial glucose and inflammatory cytokine IL-8 and TNF-α concentrations, which correlated with reduced triglyceride levels. The lipidomic profile exhibited significantly lower levels of triacylglycerols, phosphatidylethanolamines, diacylglycerols, and ceramides following fenofibrate administration. On histopathological analysis, we observed an aberrant amount of intraepithelial CD3+ T lymphocytes (IEL) in the small intestine of dogs with spontaneous and induced-DM. Fenofibrate reduced IEL density in the duodenum of dogs with DM and enhanced markers of intestinal barrier function in vivo and in vitro. There were minimal changes in the intestinal microbial composition following fenofibrate administration, suggesting that repair of intestinal barriers can be achieved independently of the resident microbiota. Our findings indicate that lipid metabolism is critical to functionality of the intestinal epithelium, which can be rescued by PPARα activation in dogs with DM.